2001
DOI: 10.1007/s005950170002
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Risks, and Acceptance of Total Thyroidectomy for Multinodular Benign Goiter

Abstract: Selective morphology- and function-adapted resection is generally regarded as the surgical treatment of choice for benign goiter causing iodine deficiency. This procedure aims to reduce the need for patients to undergo reoperations for recurrence by completely removing all nodules. However, to achieve this sometimes requires a total thyroidectomy, the option of which is often rejected because of a presumed higher rate of complications. In this study, 324 patients who underwent total thyroidectomy were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Therefore, it is plausible that the improvement of OSA by thyroidectomy in this patient helped alleviate her nocturnal bradycardia and sinus pauses. Notably, consistent with the majority of benign goiters, the patient was euthyroid [ 13 ].…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, it is plausible that the improvement of OSA by thyroidectomy in this patient helped alleviate her nocturnal bradycardia and sinus pauses. Notably, consistent with the majority of benign goiters, the patient was euthyroid [ 13 ].…”
Section: Discussionsupporting
confidence: 57%
“…Mishra et al demonstrated an 0.8% permanent RLN rate and 1.6% permanent hypoparathyroidism rate whilst Müller et al found a 0.9% rate for both morbidities [21, 22]. Many other studies confirmed similar findings [23–25].…”
Section: Discussionmentioning
confidence: 78%
“…In addition, surgical techniques for benign thyroidal disorders have improved greatly over the past several years and postoperative morbidity and mortality rates have further decreased. Life-threatening complications, such as postoperative bleeding, hematoma, compression of air passages or suffocation, can be avoided in most patients (Colak et al, 2004;Müller et al, 2001). In the light of these improvements, the value of drainage in thyroid surgery might be newly questioned.…”
Section: Resultsmentioning
confidence: 99%